STRATEGI BERTAHAN PEDAGANG BATU CINCIN PASAR RAYA KOTA PADANG - ZULFIKAR, MUHAMMAD - (Pendidikan Sosiologi, 2014)
The number of traders who are in the stone ring Pasar Raya Padang precisely along Jalan Nusantara Building Gang in 2012 amounted to as many as 50 traders stone ring. Traders who trade stone ring along Jalan Nusantara Building Gang must maintain its business with the competition along with other traders. The competition among the merchants of accessories which are goods produced by factories that sell items such as rings, necklaces, bracelets and other accessories. Competition with fellow traders stone ring also occur where there is a stone ring merchants are also selling counterfeit goods or print a stone that is not a natural rock but the rock is made of glass and the like are also good. The purpose of this study is to describe how the coping strategies of traders stone ring Pasar Raya Padang. The theory that I use in this study is the theory of social action with the type of instrumental rational action. An action can only be said of social action where such action is done by considering the behavior of others and oriented to the behavior of others. This study used qualitative methods, while this type of research is descriptive. The informants were taken by purposive sampling with six people informant. Technique data collection by observation, direct interviews and documentation. Models and Data Analysis using Milles and Huberman. The results of this study are survival strategies merchant stone ring 1). Lobbying, visitors or prospective buyers who come to the stall or where he traded, 2). prices offered to consumers is relatively low, 3). Models and new types of goods, and 4). The use of machine tools. Four strategies were used by the merchant stone ring in Pasar Raya Padang in maintaining its business, the four strategies proven effective with the presence of a ring of stone merchant, which is still located along Jalan Gang Nuantara Building is still able to survive.